PREDICTING DIABETES DISTRESS in PATIENTS WITH TYPE 2 DIABETES: A LONGITUDINAL STUDY - Fisher, Lawrence (2009)
OBJECTIVE: Diabetes distress (DD) is a condition distinct from depression that is related to diabetes outcomes. In those without distress initially, little is known about what indicators place patients at risk for subsequent distress over time. RESEARCH DESIGN AND METHODS: From a community based, 3-wave, 18-month study of type 2 diabetic patients (N = 506), we identified patients with no DD at T1 who displayed DD at T2, T3 or both (N=57). Using logistic regression with full and trimmed models, we compared them to patients with no DD at all 3 time points (N = 275) on three blocks of variables: patient characteristics (demographics, depression, extra-disease stress), biological (HbA(1c), BMI, comorbidities, complications, blood pressure, non HDL cholesterol), and behavioural variables (diet, exercise). Selected interactions with stress and MDD were explored. RESULTS: The odds of becoming distressed over time were higher for being female, previously having MDD, experiencing more negative events or more chronic stress, having more complications, and having poor diet and low exercise. Negative life events increased the negative effects of both high HbA(1c) and high complications on the emergence of distress over time. CONCLUSIONS: We identified a list of significant, independent direct and interactive predictors of high DD that can be used for patient screening to identify this high risk patient cohort. Given the impact of high DD on diabetes behavioural and biological indicators, the findings suggest the usefulness of regularly appraising both current life and disease-related stressors in clinical care.